AB0476 GIANT CELL ARTERITIS: A DISEASE WITH DIFFERENT SUBSETS. (2nd June 2020) - Fernández, E.; Monjo, I.; Bonilla, G.; Peiteado, D.; Plasencia, C.; Balsa, A.; De Miguel, E.
Abstract : Background: Giant cell arteritis (GCA) is the most common form of autoimmune vasculitis in the elderly. Some evidence indicates that GCA is a heterogeneous disease in terms of symptoms, immune pathology and response to treatment 1 . Objectives: To analyze whether the identification by image of cranial vessels (VC) or large vessels (VG) involvement allows to characterize different clinical subsets of the disease. Methods: Descriptive observational study of the last 87 consecutive patients with a new diagnosis of GCA in our hospital. All patients had a CV and LV CDUS exam that included axillary, subclavian, vertebral and carotid arteries or a Positron Emission Tomography (PET-CT). The OMERACT (Outcome Measures in Rheumatology) definitions of halo sign were used for ultrasound diagnosis and IMT limits were established as ≥ 0.34 mm for superficial temporal arteries and ≥ 1 mm for axillary, subclavian and carotid arteries; a clear halo sign was used in the vertebral arteries. The radiologist's report and the liver/vascular wall index were used for the definition of positive PET-CT. The medical records of these patients were reviewed and their demographic, clinical and laboratory data were compared between the different patterns of GCA. The statistical significance limit was set at P < 0.05. Statistical analyses were performed by using SPSS version 25. Results: Out of 198 patients with suspected GCA who underwent a CDUS or PET-CT between November 2016 and November 2019, 87 were diagnosed of GCA. Three different patterns were detected: 44 patients (50.6%) had an exclusive cranial pattern, 31 (35.6%) had a mixed pattern with involvement of both CV and LV and 12 (13.8%) had an exclusive large vessel pattern. The differences between these 3 subsets are shown in table 1 . Patients with a LV pattern had more fever and polymyalgia rheumatica than patients with CV involvement and fewer ischemic visual disturbances than those with mixed pattern, reaching statistical significance. In addition, they tended to have fewer other ischemic symptoms (headache, jaw claudication) and more general symptoms than patterns with CV involvement. Regarding laboratory values, the erythrocyte sedimentation rate was significantly higher in the exclusive CV involvement group and lower in those with only LV involvement. Conclusion: Imaging in GCA allow us to establish different patterns of involvement (cranial, mixed, large vessel) that correspond to different clinical subsets. The patients with LV subset debut with a lower ESR and have more fever and polymyalgia rheumatica and less ischemic symptoms. References: [1]van der Geest KSM, Sandovici M, van Sleen Y, et al. Review: What Is the Current Evidence for Disease Subsets in Giant Cell Arteritis?. Arthritis Rheumatol. 2018;70(9):1366–1376. doi:10.1002/art.40520 Disclosure of Interests: Elisa Fernández: None declared, Irene Monjo: None declared, Gemma Bonilla: None declared, Diana Peiteado: None declared, Chamaida Plasencia: None declared, Alejandro Balsa Grant/research support from: BMS, Roche, Consultant of: AbbVie, Gilead, Lilly, Pfizer, UCB, Sanofi, Sandoz, Speakers bureau: AbbVie, Lilly, Sanofi, Novartis, Pfizer, UCB, Roche, Nordic, Sandoz, Eugenio de Miguel Grant/research support from: Yes (Abbvie, Novartis, Pfizer), Consultant of: Yes (Abbvie, Novartis, Pfizer), Paid instructor for: yes (AbbVie, Novartis, Pfizer, MSD, BMS, UCB, Roche, Grunental, Janssen, Sanofi), Speakers bureau: yes (AbbVie, Novartis, Pfizer, MSD, BMS, UCB, Roche, Grunental, Janssen, Sanofi)